Corrosion Resistance at High Temperature of NiCrAlY and NiCrFeNbMoTiAl Coatings Deposited by APS - Tristancho-Reyes, José Luis; Chacón-Nava, José Guadalupe; Almeraya-Calderón, Facundo (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The corrosion at high temperature in pipes used in steam generating equipment (boilers), has been recognized as a serious problem, that results in the pipes thinning and therefore the equipments failure. In the last decade there has been a rise in investigations involving protective coatings to help, in some way to extend the useful life of these equipments. This investigation determined the NiCrFeNbMoTiAl and NiCrAlY coatings behavior, deposited by plasma-assisted thermal projection spraying (APS) on the alloy SA213 T22 (2¼Cr -1Mo), in acorrosive environment of 80 % V2O5- 20 % K2SO4 to 800 °C. The kinetics corrosion values were determined by linear polarization resistance (LPR) and electrochemical impedance spectroscopy (EIS). The results obtained show a lower kinetic corrosion on the NiCrFeNbMoTiAl coating than the NiCrAlY coating, confirmed by the SEM, Scanning Electron Microscopy.